The Importance of Family to Youth Living in Violent Communities - McDonald, Catherine C. (2011)
The purpose of this study was to investigate family functioning in the relationship between community violence exposure and 1) self-esteem and 2) confrontational coping in a sample of urban youth. Adhering to the tenets of community based participatory research, academic and community partners collaborated on a cross-sectional study with 110 community dwelling urban youth, ages 10–16 living in a city located in the Northeastern United States. As part of a larger survey, this analysis included selected items on lifetime community violence exposure, family functioning, self-esteem and use of confrontational coping strategies in response to community violence. Over 90% of the youth reported some type of lifetime community violence exposure. Controlling for age and gender, older youth and those with healthier family functioning had higher self-esteem; community violence exposure was not associated with self-esteem. Healthier family functioning was associated with decreased use of confrontational coping, though increasing amounts of community violence exposure was still associated with increased confrontational coping. Family can be protective in violent environments. Results from this study directly informed an intervention aimed at youth violence prevention. This study highlights how psychiatric and mental health nurses may be able to address the complex interplay of factors for youth living in violent environments.